L’utilisation des catéchismes en langues indigènes par les curés et vicaires d’Indiens dans l’archevêché de Mexico en 1569 - Eric Roulet (Caravelle)
The ecclesistical authorities decided to use indigenous languages for the New Spain Indians’ religious evanglization and management. Therefore the priests conceived several devices to help them with their catechesis (textbooks, sermons, catechisms). However, it’s quite difficult to determine up to what point priests used native languages. The survey ordered by the authorities from Madrid, and which was done by friar Alonso de Montúfar, Mexico’s bishop, on october 20 1569, to find out about the priests’ and vicars’ pastoral practices in his diocese, actually shows the distribution of doctrine books. Nevertheless, what it reveals about their knowledge of native languages, suggests the limits of the Indians’ religious management.